OP75 Implementing Risk Stratification In Primary Care: A Qualitative Study. (2017) - Porter, Alison; Snooks, Helen; Kingston, Mark; Davies, Jan; Hutchings, Hayley; Whitman, Shirley; Watkins, Alan; Evans, Bridie; Bailey-Jones, Kerry; Burge-Jones, Deborah; Dale, Jeremy; Fitzsimmons, Deborah; et al.
Abstract : INTRODUCTION: A predictive risk stratification tool (PRISM) to estimate a patient's risk of an emergency hospital admission in the following year was trialled in general practice in an area of the United Kingdom. PRISM's introduction coincided with a new incentive payment ('QOF') in the regional contract for family doctors to identify and manage the care of people at high risk of emergency hospital admission. METHODS: Alongside the trial, we carried out a complementary qualitative study of processes of change associated with PRISM's implementation. We aimed to describe how PRISM was understood, communicated, adopted, and used by practitioners, managers, local commissioners and policy makers. We gathered data through focus groups, interviews and questionnaires at three time points (baseline, mid-trial and end-trial). We analyzed data thematically, informed by Normalisation Process Theory (1). RESULTS: All groups showed high awareness of PRISM, but raised concerns about whether it could identify patients not yet known, and about whether there were sufficient community-based services to respond to care needs identified. All practices reported using PRISM to fulfil their QOF targets, but after the QOF reporting period ended, only two practices continued to use it. Family doctors said PRISM changed their awareness of patients and focused them on targeting the highest-risk patients, though they were uncertain about the potential for positive impact on this group. CONCLUSIONS: Though external factors supported its uptake in the short term, with a focus on the highest risk patients, PRISM did not become a sustained part of normal practice for primary care practitioners.